RIJALUL QUR’AN: (Membincang Sejarah Para Penulis Wahyu) - ‘Ulya, Kalimatul; Saidah, Saidah (QOF, 2017)
The companions of Prophet Muhammad SAW who had contributed to compile and rewrite the Qur’an is very important to be known by Muslims especially, because then we can remember who contributed to record the Qur’an. So Muslims today can easily read and memorize the Qur’an. Especially in the modern era today, the Qur’an is no longer in the form of Mushaf but has been transformed in digital form and can be downloaded for free in order to facilitate Muslims to read it so as not to be limited by space and time. But it can not be separated from the services of the companions of the Prophet who has recorded the Qur’an neatly as we read today. Therefore, this study is a literature review documenting the names of friends of the Prophet who have great merit in the bookkeeping of the Qur’an. The writers of revelation called katibu al-wahyī (the writers of revelation) recorded in some historians amounted to 26 friends. While al-halabi argues that the author of the revelation amounted to 44 friends, but there are only 10 friends who mashur well-known among the friends of the Prophet namely Abu Bakr, Umar bin khattab, usman bin Affan, Ali Bin Abi Talib, Muawiyah bin Abi Sufyan Zubayr bin al-Awam , Sa’id bin al-Ash, Amr bin al-’Ash, Ubay bin Ka’ab, Zayd bin Thabit. And of the ten companions, Zayd bin thabit wrote the most revelation of the Qur’an especially the passages revealed in Medina, because he was the personal secretary of Rosulullah.